Ultrasonography with doppler assessment of the fetus with Intrauterine Growth Restriction (IUGR) - B M Swain; P N Rautray (Wolters Kluwer Medknow Publications, 2016)
There is a strong association between stillbirth and fetal growth restriction. Early detection and management of IUGR can lead to reduced related morbidity and mortality. In this paper we have reviewed effectiveness of Doppler velocimetry for the detection and surveillance of high risk pregnancies. Serial fundal height measurement plotted on customized charts is a useful screening tool, whereas fetal biometry and Doppler flow are the mainstay for investigation and diagnosis of IUGR. Among high-risk pregnancies with suspected IUGR, the use of umbilical arterial Doppler assessment significantly decreases the likelihood of labour induction, caesarean delivery, and perinatal deaths. Ante partum surveillance with Doppler of the umbilical artery should be started when the fetus is viable and IUGR is suspected.